Politeness strategies in film: A pragmatic analysis of dialogue in “the social network” - Abdul Aziz, Abdul Kabeer; Hashim, Haida Umiera (International Journal Linguistics of Sumatra and Malay, 2025)
This qualitative content analysis explored the application of politeness strategies by characters in the 2010 film The Social Network, guided by Brown and Levinson’s (1978) politeness theory. The study systematically examined the film’s dialogue to identify instances of positive politeness, negative politeness, bald on record, and off-record strategies. Data were drawn from the official screenplay and fan-generated transcripts to ensure comprehensive coverage and contextual accuracy. A coding manual was developed to enhance consistency in identifying and categorising the strategies. The findings shed light on how language functions as a strategic tool in navigating interpersonal dynamics, power relations, and conflict within the high-pressure tech industry portrayed in the film. By addressing a gap in research on cinematic communication, the study contributes to the broader fields of pragmatics, media discourse, and communication studies. The implications suggest that politeness strategies in film not only reflect real-world communicative norms but also provide insights for screenwriters, educators, and media analysts. Future research could expand on this analysis by comparing politeness strategies across different genres or cultural contexts.